Mechanical response of natural anchors in cable logging. Issue 1 (2nd January 2021) - Marchi, Luca; Trutalli, Davide; Mologni, Omar; Gallo, Raimondo; Roeser, Dominik; Cavalli, Raffaele; Grigolato, Stefano
ABSTRACT: Cable logging is a common harvesting technique for steep slope conditions, despite the safety hazard for the operators, which is mainly related to failure of cables or anchor trees. The multiple factors that determine whether a tree should be considered as an anchor make it difficult to estimate the actual suitability of the anchor tree from a safety perspective during logging. To address this critical question, the mechanical response of natural anchors was monitored in nine cable logging sites using a standing skyline system. Different anchoring methods were observed, namely, tieback anchors, multiple in-line anchors and single tree anchors. Based on previous experience regarding tree stability assessment, an innovative continuous monitoring technique was applied at each research site. The mechanical response of the anchors was analyzed in terms of force-rotation curves, which summarize the effects of loads transmitted by the skyline. An elastic response was observed in nearly all anchors, but the magnitude of the rotation varied depending on the anchoring method and the applied force observed during the survey. Effects due to cyclic loading were analyzed in four of the case studies, and an apparent relaxation phenomenon at the root-plate system was observed. Finally, the research provides an estimation of the anchor's stability with respect to their maximum theoretical resistance, evaluated from trees showing similar characteristics that have previously been tested. Results from these field measurements provide information that can improve guidance regarding the holding strength of anchors to current empirical methods and help ensure safety anchoring methods.